Optimalisasi Kompetensi Mahasiswa melalui Instalasi dan Konfigurasi Sistem Operasi Berbasis Praktik - Kevin Kurniawansyah; Noneng Marthiawati; Hetty Rohayani; Hafiz Nugraha (Journal of Social Responsibility Projects by Higher Education Forum, 2026)
This community service activity aims to improve students’ competencies in the installation and configuration of operating systems through a practice-based approach at Universitas Muhammadiyah Jambi, involving 25 participants. The problem faced by the participants is the low level of practical skills in independently performing operating system installation and configuration, caused by the dominance of theoretical learning and the lack of direct practical experience. Therefore, a learning approach that integrates theoretical and practical aspects in a balanced manner is required. The method used in this activity is hands-on training combined with direct mentoring through the stages of preparation, implementation, evaluation, and follow-up. During the implementation stage, participants were provided with basic materials, demonstrations, and direct practice under the guidance of the implementation team. Evaluation was carried out by comparing pre-test and post-test results as well as observing participants’ skills during the activity. The results show a significant improvement in students’ competencies, indicated by the transition from conceptual understanding to the ability to independently perform installation and configuration of operating systems. In addition, participants demonstrated improvement in basic troubleshooting skills, learning engagement, and confidence during practice. This activity produced outputs in the form of improved technical skills relevant to industry needs and the development of independent problem-solving abilities among students. Therefore, practice-based training methods are proven to be effective in improving student competencies in the field of information technology and have the potential to be further developed in advanced training programs.